Paula Nadelstern's kaleidoscope quilts : an artist's journey continues. - Nadelstern, Paula (Lafayette, CA : C & T Pub., 2008)
"Book features 19 Nadelstern Kaleidoscope quilts, 18 of which have not been previously published. Author also includes comprehensive technique and design chapters detailing her unique style and philosophy"--Provided by publisher.
Quilt gallery -- The artful kaleidoscope -- The technical kaleidoscope -- Workbook.
Includes index.
Keywords: Quilting -- Patterns; Patchwork -- Patterns; Kaleidoscopes in art